Power and entitlement: Addressing the structural drivers of food insecurity and malnutrition - Helen Walls; Martin McKee (PLOS Global Public Health, 2026)
The world produces enough food for all, yet it falls short of providing a nutritionally balanced diet, and what it produces is extremely unevenly distributed, with high levels of undernourishment and obesity co-existing, often within the same countries. Policy responses have achieved only limited success because they often fail to address the underlying causes of these outcomes. Drawing on Amartya Sen’s entitlement framework and adapting it by making the conditions governing conversion analytically explicit, we explain food access in terms of people’s endowments and the exchange, production, and transfer entitlements through which food is acquired. We examine two analytically distinct but mutually reinforcing forces: corporate power and wealth inequality. Corporate concentration can reshape production, supply chains, food environments and public policy, while wealth inequality limits access to productive assets, purchasing power and social protection. We argue that durable progress requires policies that rebuild household endowments, constrain excessive corporate and political power, strengthen conversion factors, and widen exchange, production and transfer entitlements. Priority measures include progressive taxation of income and particularly taxation of extreme wealth, social protection, competition and governance reform, secure land tenure and support for smallholders, regulation of food marketing, and investment in enabling infrastructure.